Aggregate Formation During the Viral Lysis of a Marine Diatom - Yamada, Yosuke; Tomaru, Yuji; Fukuda, Hideki; Nagata, Toshi (Frontiers in Marine Science, 2018)
Recent studies have suggested that the viral lysis of microbes not only facilitates the conversion of particulate organic matter into dissolved organic matter, but also promotes the formation of organic aggregates, which enhance the export of organic carbon from the surface ocean to the deep sea. However, experimental data supporting this proposition are limited. Here, we tested the hypothesis that the viral infection of marine diatoms enhances aggregate formation. We used a model system consisting of Chaetoceros tenuissimus, a bloom-forming diatom with an approximate cell size of 3–10 μm, and a DNA virus, CtenDNAV type II, which replicates in the nucleus of C. tenuissimus. The volume of large particles (50–400 μm in equivalent spherical diameters, determined from photographic images) was measured over time (up to 15 days) in the diatom-alone control and a virus-added diatom culture. We also determined the concentrations of Coomassie-stainable particles (CSP, proteinaceous particles) and transparent exopolymeric particles (TEP, acid-polysaccharide-rich particles) with colorimetric methods. The total volume of large particles was significantly higher (5–59 fold) in the virus-added diatoms than in the diatom-alone control during the period in which the viral lysis of the diatoms proceeded. One class of large particles produced in the virus-added diatoms was flake-shaped. The flakes were tightly packed and dense, and sank rapidly, possibly playing an important role in the vertical delivery of materials from the surface to the deep sea. The bulk CSP concentrations tended to be higher in the virus-added diatoms than in the diatom-alone control, whereas the reverse was true for the TEP. These results suggest that proteinaceous polymers are involved in aggregate formation. Our data support the emerging notion that the viral lysis of microbes facilitates aggregate formation and the export of organic carbon in the ocean.